Strategi Pembelajaran Tahsin dan Pengembangan Motorik Halus Anak Usia Dini di TK Aisyiyah Pucangan 1: Tahsin Learning Strategy and Early Childhood Fine Motor Development at Aisyiyah Pucangan 1 Kindergarten - Dwi Heni Hendryati; Arlena Maudina; Defia Eka Alpianti; Filsa Vania Pradisti; Nurulita Aulia Indriyani; Cynthia Indah; Salsabil Fadiyah; Ahmad Nurrohim (Litera Academica Publishing, 2025)
PKLPP activity at TK Aisyiyah Pucangan 1 aims to strengthen character education and develop early childhood basic skills through tahsin learning strategies and fine motor skill development. Tahsin learning was carried out through group recitation (murojaah) and turn-taking performance methods to improve Qur’an reading abilities. Meanwhile, fine motor skills mosaic-making art activity that trained hand-eye coordination, precision, and creativity. This activity demonstrates that collaboration between educational institutions, students, and learners can create an active, enjoyable, and meaningful learning environment, contributing significantly to the improvement of early childhood education quality.